President Abdurrahman Wahid’s Policy Against Chinese Indonesians in 1999-2001 - Alamsyah, Adi Wildan; Marjono, Marjono; Umamah, Nurul; Sumardi, Sumardi; Surya, Riza Afita (JURNAL HISTORICA, 2022)
President Abdurrahman Wahid's policy emerged because of discrimination against ethnic Chinese in Indonesia. The uniqueness of this research is because Abdurrahman Wahid is the first President of Indonesia to implement a policy of pluralism in comparison to the previous government. This study aims to find out and understand the way the government of Abdurrahman Wahid seeks to equalize the rights of ethnic Chinese citizens with other ethnicities, and what impacts it has. This research is expected to become educational information for historical researchers and can be developed by other historians. The research method used is historical research which includes heuristics, verification, interpretation, and historiography. The approaches and theories used are political sociology and public policy theory. The results obtained from this study are the genesis of President Abdurrahman Wahid's policies, the manifestation of President Abdurrahman Wahid's policies in the social, cultural, political fields, and the impact of these policies.